MISOPROSTOL FOR INDUCTION OF LABOR IN TERM PREGNANCY - Gede Angga Permana AW; Putera Kemara; I Wayan Megadhana (E-Jurnal Medika Udayana, 2014)
Induction of labor refers to the process whereby uterine contractions are initiated bymedical or surgical means before the onset of spontaneous labor. Several studies haveshown that continuous intravenous infusion of oxytocin is less efficient, particularlywhen there are unfavorable cervical conditions, leading frequently to a cesarean section,because of induction failure. Misoprostol is a cervical modifying agent and laborinductor. The typical effect of a single dose of oral misoprostol is an increase in uterinetonus. Sustained plasma level of misoprostol is required for the development of regularcontractions appear. The bioavailability of vaginal misoprostol also greater compared tooral, sublingual and rectal administration. Using misoprostol for cervical ripening andlabor induction represented a 47% reduction in the risk of having a cesarean section(risk ratio = 0.53). In cases of unfavorable cervix condition, the use of misoprostolcould produce several beneficial effects compared to other inductor such as oxytocin